Administrative and leadership requirements for implementing evidence-based practices in special education programs: the perspective of special education teachers - Alsuhaymi, Abdulaziz; Alhammadi, Muteb; Eltantawy, Mahmoud Mohamed (Frontiers in Education, 2024)
Administrative and leadership requirements are crucial to the application of evidence-based practices (EBPs) in special education. Therefore, the current study aimed to assess the availability of administrative and leadership requirements for applying EBPs in special education programs from the teachers' perspective, as well as determine the differences in their availability depending on the variables of disability category (intellectual disability (ID), autism spectrum disorder (ASD), and learning disabilities (LDs)) and school stage (e.g., primary or middle school). The sample included 243 special education teachers working in the city of Riyadh, Kingdom of Saudi Arabia. A questionnaire on the administrative and leadership requirements for implementing EBPs in special education programs (prepared by the researchers) was used to collect data. The results revealed the availability (which ranged from moderate to high) of administrative and leadership requirements for implementing EBPs. Moreover, there were differences in the availability of administrative and leadership requirements according to students' disability category; these differences were in favor of the learning disability group. However, there were no differences according to the academic stage. We recommend conducting further research on administrative and leadership requirements using different methods.